Synthesis, Characterization and Biological Activity of New Derivatives of Hetrocyclic Compound - Athraa B. Mohamad (Journal of Global Pharma Technology, 2019)
This study included the preparation and characterization of a series of new derivatives of  pyrazoline, isoxazoline by two steps the first step involved the preparation of chalcones by reaction between aldehyde and acetophenone the second step involved the react of chalcones two stepe react chalcones with hydrazine to form pyrazoline also chalcones was reacted with hydroxylamine hydrochloride in present a basic medium for the preparation of the derivative isoxazoline The derivatives has shown moderate to good activity against gram-positive bacteria (Staphylococcus aureus), gram-negative bacteria (Escherichia coli)  when compared with standard antibiotic gentamycin .all prepared compounds were diagnosed by spectra of H1-NMR, mass.Keywords: Isoxazolin, Pyrazoline, Chalcones, Synthesis, Biological activities.